"Plemię żmijowe" (Łk 3,7) i pokrewne wypowiedzi w Łk-Dz. Diagnoza sytuacji współczesnych Jezusowi czy kondycji człowieka? - Mielcarek, Krzysztof (The Biblical Annals, 2018)
The negative phrase: “the brood of vipers” has no equivalent in the OT, neither it is present in the extra-biblical writings. The first evangelist is the one who uses the epithet most often. However, Luke does use it as well (Lk 3:7). The paper is a study of narrative strategies of both Gospel-writers within the context of the OT and the rabbinic literature in order to identify one of the important narrative threads of the third Gospel. Instead of stigmatizing the particular faction of the Israel’s religious society, Luke employs the primordial Christian tradition to stress sinfulness of human nature, which in the past resulted in rejecting the good news of Jesus.